The Insurance Hypothesis and Market Prices - Menon, Krishnagopal; Williams, David D. (The Accounting Review, 1994)
[The literature on the audit market has suggested that a valued attribute of audits is implicit insurance. The insurance stems from the investor's right to recover from auditors the losses sustained by relying on audited financial statements that contain misrepresentations. This "insurance hypothesis" has proven difficult to test empirically, despite the widespread evidence of litigation against auditors. In this paper we provide some empirical support, showing that investors assign a value to the right to recover investment losses from the auditor. We examine the effect on stock prices of Laventhol & Horwath (L&H) clients of two related events: first, the disclosure of their auditor's bankruptcy, and second, the appointment of a successor auditor. L&H's bankruptcy is a rare instance in which the insurance protection provided by the auditor was suddenly withdrawn and the ability of investors to recover losses from the auditor was significantly curtailed. We argue that the value assigned by investors to the right to recover potential losses from the auditor is a component of the stock price, and hypothesize that it varies with the likelihood that the right will be exercised. It is expected to increase with increasing magnitude of stock price declines and to be greater for recent initial public offerings (IPOs) than for seasoned securities. The results suggest that the disclosure of L&H's bankruptcy had an adverse effect on market prices of L&H clients. As hypothesized, the effect varied with previously incurred price declines, and was greater for IPOs. To more distinctly separate insurance and monitoring effects, we also examined the market reaction to clients' announcements of a replacement auditor. No significant reaction was observed, which is consistent with the insurance hypothesis. Overall, the results of the paper provide some empirical support for the theory that investors view the audit product as including insurance against potential investment losses.]